The Multi-Dimensional Research Agendas Inventory – Revised (MDRAI-R): factors shaping researchers’ research agendas in all fields of knowledge - Horta, H. (2020)
This study creates a novel inventory that characterizes factors influencing the research agendas of researchers in all fields of knowledge: the Multi-dimensional Research Agendas Inventory-Revised (MDRAI-R). The MDRAI-R optimizes an initial inventory designed for the social sciences (the MDRAI) by reducing the number of items per dimension, improving the inventory’s psychometric properties, and including new dimensions (“Academia Driven” and “Society Driven”) that reflect the greater influence of social and organizational structures on knowledge production and demands for research impact. This inventory enhances our ability to measure research activities at a time when researchers’ choices matter more than ever, and it will be of interest to researchers, policy makers, research funding agencies, and university and research organizations.